Macro-Environmental Analysis Throughout Covid-19 Pandemic Using Pestel Framework: A Study in Indonesian Multi-Industry - Siti Paramadita; Lorio Purnomo; Stefanus Rumangkit (Komunitas Dosen Indonesia, 2024)
To become competitive, companies cannot rely solely on their internal factors. Macro-environmental factors have become essential for companies. These factors can be analyzed using PESTEL analysis, which shows how political, economic, social, technological, environmental, and legal aspects can affect the industry. This study examines the PESTEL framework for three industries affected by COVID-19: aviation, education, and technology. The method used is case studies where the PESTEL framework analyzes the industrial competitiveness of those three industries. The results show that each sector has different characteristics and that PESTEL factors have various effects. This study gives insights into what kind of macro-environmental factors are crucial for the industries and how companies should act to maintain their competitiveness in the industry. Additionally, risk analysis is used within this study to help companies raise their business performance and function better amidst the COVID-19 pandemic. The findings reveal that political and environmental factors significantly impact the aviation industry, social and technological factors influence the education sector, and economic and technological factors drive the e-commerce industry. This comprehensive analysis highlights the need for tailored strategies for each industry to navigate external challenges effectively. The limitation of this study is the lack of primary data. Therefore, future research using surveys or interviews can enrich this study. By understanding these dynamics, companies can develop more robust strategies to thrive in a post-pandemic world.